Platelet-Cancer Interplay: Molecular Mechanisms and New Therapeutic Avenues - Braun, Attila; Anders, Hans-Joachim; Gudermann, Thomas; Mammadova-Bach, Elmina (Frontiers in Oncology, 2021)
Although platelets are critically involved in thrombosis and hemostasis, experimental and clinical evidence indicate that platelets promote tumor progression and metastasis through a wide range of physical and functional interactions between platelets and cancer cells. Thrombotic and thromboembolic events are frequent complications in patients with solid tumors. Hence, cancer modulates platelet function by directly inducing platelet-tumor aggregates and triggering platelet granule release and altering platelet turnover. Also, platelets enhance tumor cell dissemination by activating endothelial cell function and recruiting immune cells to primary and metastatic tumor sites. In this review, we summarize current knowledge on the complex interactions between platelets and tumor cells and the host microenvironment. We also critically discuss the potential of antiplatelet agents for cancer prevention and treatment.